PWE-016 Can the Response to Posterior Tibial Nerve Stimulation for Faecal Incontinence Predict the Response to Sacral Nerve Stimulation?. (4th June 2013) - Thomas, G; Dudding, T; Nicholls, R J; Vaizey, C
Abstract : Introduction: Sacral nerve stimulation (SNS) is an established treatment for faecal incontinence (FI). Posterior tibial nerve stimulation (PTNS) is a more recent and increasingly popular treatment for FI. PTNS is cheaper, safer and as effective as SNS in the short term. PTNS can be used as an initial therapy, with SNS reserved for those who have failed to improve. The aim of this study was to see if the response to PTNS can be used to predict the response to SNS. Methods: Prospectively collected data for all patients who had undergone transcutaneous PTNS followed by SNS were analysed. A good clinical response to PTNS and to SNS was defined as a ≥50% reduction in frequency of FI episodes per week. Results: Ten patients underwent PTNS followed by SNS for FI. Three patients had a poor response to PTNS. Two of these had a subsequently had a poor response to SNS. Seven patients had a good response to PTNS. Five of these had a good response to SNS. Conclusion: This small study suggests that the response to PTNS may predict the response to SNS. Much larger studies are needed to explore this further. Disclosure of Interest: None Declared.